ANALISIS PENGEMASAN JAGUNG MANIS (ZEA MAYS L. SACCHARATA STURT) BERKELOBOT DENGAN BERBAGAI BAHAN PENGEMAS - Renny Anggraini; Tuti Sugiarti (FoodTech: Jurnal Teknologi Pangan, 2018)
Decrease in quality of sweet corn during distribution or storage could be represented by decrease of sugar as a result of continously repiration. Packaging could significantly reduces postharvest respiration and transpiration rate of crops and also extend its shelf life. This study aimed to determine the best primary packaging during disribution of sweet corn. Results of the study showed that polypropylene was the best primary packaging for husked corn during distribution and storage.